Spatial distribution and associated factors of zero-dose immunization among 12-23 month-old children in Ethiopia: spatial and survey regression analysis - Muchie, Kindie Fentahun; Azene, Abebaw Gedef; Bogale, Kassawmar Angaw; Asmamaw, Desale Bihonegn; Negash, Wubshet Debebe; Belachew, Tadele Biresaw; Tarekegn, Bethelihem Tigabu; Terefe, Bewuketu; Bantie, Getasew Mulat; Eshetu, Habitu Birhan; Wassie, Gizachew Tadesse (BMC pediatrics, 2025)
Immunization is one of the public health interventions, saving millions of lives. Despite this, many children, especially those living in low- and middle-income countries, continue to miss out on lifesaving vaccines, the worst of which is zero-dosage. It is crucial to identify individuals and obtain timely, reliable information on their geographic distribution and related attributes to support spatially tailored strategies and interventions. Undoubtedly, assessing zero-dose prevalence is an input to achieve the WHO’s 2030 agenda, which attempts to reduce the number of zero-dose children. Hence, this study aimed to determine the prevalence, spatial distribution and associated factors of zero-dose immunization among children in Ethiopia.
Gesehen am 28.11.2025